2018
DOI: 10.17716/botkozlem.2018.105.1.13
|View full text |Cite
|
Sign up to set email alerts
|

Effect of N, P and K fertilization on the species succession of an established grass sward during a decade

Abstract: Eff ects of diff erent soil N, P and K supply levels and their combinations were examined on the species composition of a grass sward between 2006 and 2015 in a fi eld experiment. Th e grass was established in autumn of 2000 with seed mixture of eight grass species. Th e calcareous chernozem loamy soil of the growing site contained around 3% humus, 3-5% CaCO 3 , 20-22% clay in the ploughed layer and was originally moderately supplied with available N and K, and relatively poorly supplied with P and Zn. Th e tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…The evolution of the sward composition examined here was described earlier [42], and a previous study showed that, among the N, P and K treatments, K had the least effect on biomass production in this soil [43]. The objectives of the present study were to reveal the extent to which the soil N, P and K supplies improved the biomass production and WUE of the grass, and whether better macroelement supplies resulted in a significant biomass increase even in drier periods, when nutrient uptake may be inhibited.…”
Section: Introductionmentioning
confidence: 99%
“…The evolution of the sward composition examined here was described earlier [42], and a previous study showed that, among the N, P and K treatments, K had the least effect on biomass production in this soil [43]. The objectives of the present study were to reveal the extent to which the soil N, P and K supplies improved the biomass production and WUE of the grass, and whether better macroelement supplies resulted in a significant biomass increase even in drier periods, when nutrient uptake may be inhibited.…”
Section: Introductionmentioning
confidence: 99%